Abnormal Gyrus Rectus Asymmetry in Alzheimer’s Disease: An MRI-Based Parcellation Method - Ömür Karaca; Ahmet Arman Kibar; Burcu Aslantekin; Nermin Tepe (Brain Sciences)
Background: The gyrus rectus is a key brain region with neural connections to the entorhinal cortex and hippocampus, both of which are among the earliest areas affected in Alzheimer’s disease (AD). Investigating volumetric differences and asymmetry in this region may provide insights into disease progression. This study aimed to assess gyrus rectus volume and asymmetry in AD patients using an MRI-based parcellation method. Methods: This cross-sectional volumetric study included 25 cognitively healthy adults and 25 AD patients recruited from the Neurology Clinic of Balıkesir University Hospital. Brain MRI scans were obtained using a 1.5 Tesla MRI scanner. Volumetric measurements were computed using MRIStudio, an atlas-based image analysis program. Group differences in brain volume and asymmetry index were examined, and their correlations with Mini-Mental State Examination (MMSE) scores were evaluated. Results: AD patients exhibited significantly greater rightward volumetric asymmetry of the gyrus rectus volume than healthy controls (p < 0.05). Additionally, a positive correlation was observed between gyrus rectus volume and MMSE scores (p < 0.05). Conclusions: These results suggest that rightward volumetric asymmetry of the gyrus rectus may represent a promising biomarker for tracking the progression of Alzheimer’s disease. Detecting asymmetry in brain structures could improve understanding of AD pathology and aid clinical evaluation.